Cover Image, Volume 57, Issue 2. Issue 2 (24th February 2019) - Kiyonari, Hiroshi; Kaneko, Mari; Abe, Takaya; Shioi, Go; Aizawa, Shinichi; Furuta, Yasuhide; Fujimori, Toshihiko
Abstract : The cover image is based on the Research Article Dynamic organelle localization and cytoskeletal reorganization during preimplantation mouse embryo development revealed by live imaging of genetically encoded fluorescent fusion proteins by Hiroshi Kiyonari et al., DOI:10.1002/dvg.23277 .